Cross-border effects of capacity remuneration mechanisms: The Swiss case - Florian Zimmermann; Andreas Bublitz; Dogan Keles; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2019)
In this article, cross-border effects of different market design options are analyzed using Switzerland as a case study, which is strongly interconnected to larger neighboring markets. An investigation is conducted with an agentbased model where in one scenario all market designs are represented according to the current legislation, and in another, energy-only markets (EOM) are assumed in all considered countries. The results show that wholesale electricity prices are highly dependent on the chosen market design and in the annual average up to 27% higher in the EOM scenario. Due to expected larger interconnector capacities, this increase is evident in all simulated markets. Further, the results indicate that the planned market design changes in the neighboring countries decrease investments in Switzerland. However, generation adequacy is still guaranteed due to the high Swiss hydropower storage capacity. Our results suggest that, under the current circumstances, a domestic mechanism in Switzerland is not required.
Keywords: 330; Capacity remuneration mechanisms; Cross-border effects; Electricity market coupling; Generation adequacy; Switzerland; Agent-based modeling